Mediate co-authored and determination of the state structure in the investigation of international crimes - Gamboa Rubiano, Sandra (Universidad Pedagógica y Tecnológica de Colombia, 2011)
From a dogmatic conception of criticism, the figures of co-authored and authored medi ate are revised, observing the implementation of its components under the guise of co authored by chain of command, in the jurisprudence of the Supreme Court of Justice in Colombia. In this verification it is extracted the utility of the central figure, not only as a means of responsibility, but also for the investigation and punishment of state crimes in Colombia.